Detection of Vancomycin-Resistant Enterococci (VRE) Genes in Imported Canary (Serinus canaria) Faeces - Dina Agylia Rahmandari; Mustofa Helmi Effendi; Yulianna Puspitasari; Eduardus Bimo Aksono Herupradoto; Lilik Maslachah; Boedi Setiawan; Fifin Kurnia Sari; Tri Endah Purbowati; Izzatul Istiana (Universitas Airlangga, 2026)
Antibiotic-resistant Enterococcus is currently one of the leading causes of nosocomial infections worldwide. Multidrug-resistant (MDR) Enterococcus is an important nosocomial pathogen and represents a growing clinical challenge. This study aimed to determine the presence and characteristics of Vancomycin-Resistant Enterococci (VRE) genes in the faeces of imported canaries (Serinus canaria) to assess their potential impact on animal health and the spread of antimicrobial resistance. A total of 150 canary faecal samples were randomly collected from a single importer. Colonies with Enterococcus-like morphology were identified at the genus level based on culture characteristics, Gram staining, catalase testing, and bile-esculin testing. Species identification was confirmed through carbohydrate fermentation tests. Antibiotic susceptibility testing was performed using the Kirby–Bauer method on Mueller–Hinton agar. Polymerase chain reaction (PCR) testing was subsequently conducted to identify the vanB gene. Among the samples, 39 (26%) were positive for Enterococcus faecalis. Of these isolates, 7 (17.9%) were identified as multidrug-resistant (MDR), and 5 (71.4% of MDR isolates) were classified as VRE. One of the five VRE isolates (20%) was found to carry the vanB gene, an important determinant of vancomycin resistance. These findings indicate that imported canaries may serve as reservoirs of antimicrobial-resistant bacteria with the potential to spread to the environment, other animals, and humans through the faecal–oral route or environmental contamination.